Fecal Microbiota Transplant in Refractory Cases of Pseudomembranous Colitis. A Propouse of a Clinical Case (Revista de Medicina Clinica, 2022)
Introduction: Pseudomembranous colitis is an inflammatory affectation of the mucosa of the intestine, characterized by the formation of whitish plaques. It is associated with Clostridium difficile infection, it can be associated with other infections, with other non-infectious pathologies and without known cause. Case Report: A 34-year-old male with a history of post-traumatic paraplegia who presented with an ulcerative lesion in the dorsal region, so they entered the local hospital where they indicated Meropenem, abdominal distension appeared, associated with generalized pain, absence of stools and vomiting. In the cardiopulmonary examination without pulmonary or cardiac alterations, at abdominal level abdominal distension associated with tympanism, absence of intestinal noises, the rest of the normal physical examination. The hematology shows an important leukocytosis. The rest of the exams were normal. He was taken to the operating room with an exploratory laparotomy which showed no alterations. He is taken to the special care area where his pseudomembranous colitis is suspected, he does not improve initially with antibiotic therapy, he chooses to perform a colonoscopy study. The findings were consistent with this diagnosis, in the aforementioned case we chose to place stool enemas transplanted for a period of 5 days with a clinical benefit. Discussion: Stool transplantation is an emerging little-known therapy, we consider it fundamental to conduct studies in our country because of its importance in the future in the management of pseudomembranous colitis in those cases where there is refractoriness to treatment.
Keywords: Colitis, fecal, Transplantation, Antibiotic, Sepsis.